Properties of magnetic reconnection in MHD turbulence - Servidio, S. (2010)
Numerical simulations of two-dimensional Magnetohydrodynamic (2D MHD) turbulence reveal the presence of a huge number of sites where magnetic reconnection locally occurs. The properties of this ensemble of reconnection events, that are spontaneously generated by turbulence, have been studied. The associated reconnection rates, computed as the electric field at the neutral points, are broadly distributed and the statistics of these events are presented. This new description of reconnection is relevant for space and laboratory plasmas, where generally turbulence is present. © 2010 American Institute of Physics.